2012
DOI: 10.1186/1475-2859-11-58
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurements of IPTG enable analysis of the induction behavior of E. coli in high cell density cultures

Abstract: Background: The E. coli lac operon and its components have been studied for decades, and lac-derived systems are widely used for recombinant protein production. However, lac operon dynamics and induction behavior remain the paradigm of gene regulation. Recently, an HPLC-MS-based method to quantify IPTG in the medium and inside the biomass has been established, and this tool may be useful to uncover the lack of knowledge and allow optimization of biotechnological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 34 publications
4
27
0
1
Order By: Relevance
“…Results (see Figure 2B-C) showed that IPTG is not degraded in this condition and the inducer disappearance in the medium of MG1655-Z1 was actually due to uptake by LacY. These results confirm the high stability of the IPTG molecule, previously found in literature in different conditions [16,19,20], and the role of lactose permease in IPTG uptake by LacY + strains. None of the tested environmental factors have been found to affect IPTG stability.…”
Section: Resultssupporting
confidence: 87%
“…Results (see Figure 2B-C) showed that IPTG is not degraded in this condition and the inducer disappearance in the medium of MG1655-Z1 was actually due to uptake by LacY. These results confirm the high stability of the IPTG molecule, previously found in literature in different conditions [16,19,20], and the role of lactose permease in IPTG uptake by LacY + strains. None of the tested environmental factors have been found to affect IPTG stability.…”
Section: Resultssupporting
confidence: 87%
“…Thus, each inducer takes on average 31.7 min (with 90% confidence, between 18 min and 104 min) to travel from the periplasm to the cytoplasm. Meanwhile, the leaky expression of the target gene (prior to induction) can be estimated to be B0.03 RNA per h per cell (using (12)), in agreement with the measured leakiness (o0.1 RNA per h per cell). 5,43 As a side note, the stochasticity of these events is also visible from the data.…”
Section: Transport Rate Of Iptg Through the Inner Membranesupporting
confidence: 65%
“…Due to the high rate of the forward reaction and inducer abundance, when the intracellular inducer concentration changes, we assume that reaction (12) reaches equilibrium before any binding event between R and Pr (1) can occur. Due to the high rate of the forward reaction and inducer abundance, when the intracellular inducer concentration changes, we assume that reaction (12) reaches equilibrium before any binding event between R and Pr (1) can occur.…”
Section: Model Of Inducer Repressor Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13 Several solutions to reduce the metabolic burden by adapting the induction strategy were reported. In general, the inducer concentration can be reduced to decrease the product formation rate, [14][15][16][17] the optimal IPTG to biomass ratio can be identified, 19,20 and the inducer can be fed to the reaction mixture during expression phase to adapt the cells to recombinant protein expression. 13,[21][22][23] Nevertheless, the optimal induction strategy for many target proteins differ significantly.…”
Section: Introductionmentioning
confidence: 99%